Estimation of heart rate recovery from field rides (Journal of Science and Cycling, 2024)
Heart rate recovery (HRR) is a measure of time required for the heart to resume its resting heart rate (HR) after a maximal intensity exercise load. Quicker recovery has been associated with better cardiorespiratory fitness (CRF). Therefore, HRR can be regarded as a fitness indicator and may serve as a tool to monitor the performance potential of an athlete as well as to optimize the training schedule.